Bakri Balloon in the Management of Postpartum Hemorrhage: A Review - Wright, Cara E.; Chauhan, Suneet P.; Abuhamad, Alfred Z. (American Journal of Perinatology, 2014)
Objective The purpose of this review is to ascertain the indications, techniques, and the associated morbidity with the use of Bakri balloon.Material and Methods A literature search using the PubMed database was conducted from 2001 to 2013. We calculated 95% confidence intervals (CIs) for complications.Results We identified 12 publications that met the inclusion criteria. Four reports provided the frequency of Bakri use during the study period, with the overall rate being 0.20% (138/69, 174; 95% CI, 0.17–0.25%). Two-thirds of use followed cesarean delivery (67%; 182/273). Uterine atony was specified as the underlying etiology of postpartum hemorrhage in 75% (9/12) of publication. The rate of balloon displacement was 10% (95% CI, 6–16%) and need for transfusion, 43% (95% CI, 32–55%). Hysterectomy was undertaken in 6% (95% CI, 4–10%).Conclusions There is a paucity of publications on Bakri balloon. Before its utilization is recommended in guidelines, a randomized clinical trial comparing uterotonics alone versus with balloon is warranted.
Keywords: postpartum hemorrhage; Bakri balloon; tamponade; silicone balloon